2018
DOI: 10.9789/2175-5361.2018.v10i2.334-342
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais de mulheres frente a descoberta do diagnóstico do HIV / Women social representations in face to HIV diagnosis disclosure

Abstract: Objetivo: descrever as representações sociais de mulheres diante do recebimento do diagnóstico de HIV. Método: Estudo descritivo, exploratório com abordagem qualitativa, realizado com 21 mulheres que se encontravam em dois centros de referência para pessoas que vivem com HIV/aids. Os dados foram coletados de maio a junho de 2016. Utilizou-se como referencial teórico a Teoria das Representações Sociais, e os dados foram analisados por meio da técnica de análise de conteúdo na perspectiva de Bardin. Resultados: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
2
6
0
10
Order By: Relevance
“…The discovery of HIV triggers negative feelings, such as injustice, fear, sadness, shame, terror, unbelief and surprise, and may encourage social isolation, 16 as found in this study. In this situation, the search for other health services to confirm HIV seropositivity, as reported by Pedro, may be more related to the denial of the disease than to the lack of knowledge itself.…”
Section: Discussionsupporting
confidence: 60%
“…The discovery of HIV triggers negative feelings, such as injustice, fear, sadness, shame, terror, unbelief and surprise, and may encourage social isolation, 16 as found in this study. In this situation, the search for other health services to confirm HIV seropositivity, as reported by Pedro, may be more related to the denial of the disease than to the lack of knowledge itself.…”
Section: Discussionsupporting
confidence: 60%
“…Na categoria Capacitação dos profissionais de saúde, dez artigos evidenciaram o despreparo e, ainda, a necessidade de capacitação dos profissionais para o oferecimento de atendimento em saúde adequado e humanizado. (GALVÃO et al, 2009;GONÇALVES et al, 2013;PAIVA et al, 2011;PREUSSLER;EIDT, 2007;ROMANELLI et al, 2007 MACHADO, 2009;LÔBO et al, 2018;PAIVA et al, 2011;SEIDL, 2009;GALINKIN, 2008;BISPO JÚNIOR, 2010;AYRES, 2006;SPINDOLA et al, 2015), seja por medo ou pela percepção do estigma social gerado pela doença (EID; WEBER; PIZZINATO, 2015; GALVÃO; CUNHA; MACHADO, 2009;GONÇALVES et al, 2013;NEVES;GIR, 2006;PAIVA et al, 2011;PREUSSLER;EIDT, 2007;SEIDL, 2009;GALINKIN, 2008;SPINDOLA et al, 2015;VASCONCELOS et al, 2006 No que se refere às questões sobre vida cotidiana e morte, muitas mulheres soropositivas recorreram à negação da doença como forma de proteção à discriminação em busca de manutenção da 'normalidade' de sua rotina de vida. (FARIA; PICCININI, 2015; GALVÃO;…”
Section: Metodologiaunclassified
“…Tal fato torna importante a reflexão que viver com HIV não anula o desejo pela maternidade. (SANTOS; BISPO JÚNIOR, 2010;LÔBO et al, 2018) Com o aumento da infecção entre mulheres em idade reprodutiva, é necessário ouvir e acolher soropositivas sobre temas relacionados à gestação e maternidade, o que pode resultar na diminuição do risco de transmissão vertical 6 (TV) e de agravos à saúde. (SILVA; ALVARENGA; AYRES, 2006) Assim, este trabalho teve como objetivo compreender como mulheres vivendo com HIV vislumbram a maternidade e a possibilidade de gerar bebês.…”
Section: Introductionunclassified
“…Self-doubt, low self-esteem, feelings of prejudice, and loneliness result from disclosing one's HIV/AIDS status to others. Nonetheless, it is the foundation for getting medical therapy, care, and psychological support, as well as avoiding self-blaming and nonadherence and promoting improved health [14]. A cross-sectional study conducted in northern and southern Ethiopia [11,15] showed that those patients of female gender had two times more likely to develop perceived stigma than males.…”
Section: Introductionmentioning
confidence: 99%